"Listen to your body": Participants' alternative to science in online health discussions. (September 2018) - Versteeg, Wytske; te Molder, Hedwig; Sneijder, Petra
We present a discursive psychological analysis of how the idiomatic expression "Listen to Your Body" is deployed in online forum discussions about ADHD medication and aspartame. The Listen to Your Body device allows participants to demonstrate to others that they take their health seriously and for that reason avoid scientific knowledge. They contrast Listen to Your Body with "blindly following science, " presenting Listen to Your Body as the more critical and, therefore, more rational behavior. Instead of treating the idiomatic expression as "anyone's knowledge, " speakers and recipients compete for the right to own it. It is discussed what these results mean for the role of and relation between experiential knowledge ("lay expertise") and scientific expertise in online discussions about health issues.